(untitled) (Papeles, 2018)
The objective of this paper is to analyze and characterize the relationship between Sensory Modulation Disorders and Learning Disabilities based on Fundamental Learning Components and examine how this relationship determines the school prognosis of children with Epilepsy between 7 and 10 years old. Different methods were followed: the Winnie Dunn Sensory Profile and its Supplement, and The Dynamic Occupational Therapy Cognitive Assessment for Children (DOTCA-ch). A nonexperimental, transverse, correlational design was implemented. Participants were classified as Cases (Controlled and Uncontrolled Epilepsy, n = 34) and Controls (n= 54). The results show that Sensory Modulation disorders were reported in 92.05% (81/88) of the children assessed. Children with Uncontrolled Epilepsy reported behavioral responses associated to “Poor Registration”, while those in the Controlled Epilepsy group reported responses associated to “Sensory Avoidance”. The most remarkable alterations of Fundamental Learning Components were observed in the areas of Immediate Memory and Praxis. Significant relations were found between Sensory Modulation Patterns and Learning Disabilities only in the Uncontrolled Epilepsy group. As conclusion it migh be said that considerations about the learning potential of children with Epilepsy, as well as the appropriate degree of support they need, and their strategies for sensory regulation are key elements to help them to improve school prognosis and participation in their student role.